Potensi, Peluang, dan Risiko Teknologi Nano dalam Kosmetik: Inovasi, Efektivitas, dan Tantangan Keamanan - Faizah (Alpatih Harapan Semesta, 2023)
Nanotechnology in the field of cosmetics has experienced rapid development over the past four decades in developed countries, while in Indonesia, it is still in the development stage through various research and innovations. This technology offers many advantages, such as improving the performance and efficiency of cosmetic products. Nano-sized particles with a large surface area enable more effective transportation of active ingredients to the skin, enhance the efficacy of sunscreens for deeper penetration, and improve skin hydration. However, the use of nano-technology-based cosmetics also poses potential risks, including increased toxicity, inhalation risk through spray products, penetration into blood vessels, and other health impacts. This research uses the literature review method by analyzing various primary and secondary sources, including scientific journals, research reports, and regulations related to nanotechnology in cosmetics. The analysis was conducted to identify the benefits, potential risks, and the need for safety regulations in the use of nanotechnology in the field of cosmetics. The research results emphasize the importance of clear and strict regulations from the Food and Drug Administration (BPOM) regarding the safety limits of nano materials in cosmetics. This regulation provides guidance to cosmetic industry players and the public in understanding the safety standards of nano-based products, thereby supporting the development of safe and effective cosmetics in Indonesia.